Phytoremediation potential of mustard (Brassica juncea) varieties exposed to lead stress (Asian-Australasian Journal of Bioscience and Biotechnology, 2019)
While the growth of most plants is severely restricted by the toxic effects lead (Pb), some (plants) can cope with the heavy metal stress. These hyperaccumulators are used to extract (lead) from contaminated soil in a process called phytoremediation. Although some species of Brassica are widely being used as hyperaccumulators, the phytoremediation potential of many varieties of Brassica juncea (mustard) is not well understood. The present study was conducted to assess the phytoremediation potentials of 11 mustard genotypes under Pb stress. Twenty-day-old seedlings were exposed to 200 µM Pb nitrate under hydroponic conditions and grown for 60 days. The experiment was conducted following a completely randomized design with three replications.  In response to Pb stress, a significant reduction in growth of the studied traits was observed in all of the varieties. The lowest reduction for all of the studied traits including Pb accumulation was recorded in BJ DH 17. Nevertheless, the translocation of Pb from root to shoot and shoot to grain was highest in Sambal. Bioaccumulation co-efficient was highest in Sambal whereas it was lowest in BJ DH 17. Based on the results of the present study, the variety Sambal is recognized as the most suitable genotype that can be used for Pb phytoextraction.Asian Australas. J. Biosci. Biotechnol. 2019, 4 (2), 80-87